Epithelioid Hemangioendothelioma a Rare Entity Cause of Chronic Abdominal Pain: Case Report - Hala, Aouroud; Meryem, Aouroud; Errami, Adil Ait; Oubaha, Sofia; Samlani, Zouhour; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Epithelioid hemangioendothelioma is a rare entity with clinical, histological, and evolutionary features that are intermediate between hemangiomas and angiosarcomas; clinically features are generally unremarkable with a good general condition among patients. Histology remains the key for the diagnosis and the conservative treatment is the adequate option. We report the case of a 63 years old female, presented with chronic intermittent, atypical abdominal pain, unique atypical liver nodule with a histology compatible with an EHE and 1 year follow up without recurrence.